Management of type 2 diabetes in chronic kidney disease - Salim S Virani; Sankar D Navaneethan; Jefferson L Triozzi; L Parker Gregg (BMJ Open Diabetes Research & Care)
The management of patients with type 2 diabetes and chronic kidney disease (CKD) encompasses lifestyle modifications, glycemic control with individualized HbA1c targets, and cardiovascular disease risk reduction. Metformin and sodium-glucose cotransporter-2 inhibitors are first-line agents. Glucagon-like peptide-1 receptor agonists are second-line agents. The use of other antidiabetic agents should consider patient preferences, comorbidities, drug costs, and the risk of hypoglycemia. Renin–angiotensin–aldosterone system inhibitors are strongly recommended for patients with diabetes, hypertension, and albuminuria. Non-steroidal mineralocorticoid receptor antagonists, which pose less risk of hyperkalemia than steroidal agents, are undergoing further evaluation among patients with diabetic kidney disease. Here, we discuss important advancements in the management of patients with type 2 diabetes and CKD.